Answer:
The answer is
Step-by-step explanation:
The general equation of a circle is given by
where the center of the center of the circle is given by
From the question the equation is
x² + y² + 14x + 2y + 14 = 0
Comparing with the general equation above we have
2g = 14 2f = 2
g = 7 f = 1 c = 14
So the center of the circle is
The radius of a circle is given by
[tex]r = \sqrt{ {g}^{2} + {f}^{2} - c} [/tex]
where
g = 7
f = 1
c = 14
Substitute the values into the above formula
That's
[tex]r = \sqrt{ {7}^{2} + {1}^{2} - 14 } \\ r = \sqrt{49 + 1 - 14} \\ r = \sqrt{36} [/tex]
we have the final answer as
Hope this helps you